The Influence of Pyramid Discussion towards Students’ Speaking Ability - Suhandi Hasan (Universitas Lambung Mangkurat, 2021)
The objective of this study was to find out the influence of pyramid discussion towards students’ speaking ability at the eleventh grade of SMA Negeri 11 Ambon in academic year of 2016/2017. The research design was quasi-experimental within pre-tests and post-tests given to both experimental class and control class. The students in experimental class were taught by using pyramid discussion while in the control class students were taught by using group investigation.